The life of the artist Masis Armen Bakhadoryan and his still lifes - Chookaszian , Levon (History and Culture, 2025)
Masis Armen Bahadoryan or Armen Bahadur is one of those artists who, due to the will of circumstances, remained in the shadows and was forgotten. He is completely unknown in the Armenian Diaspora and in Armenia. He is an Armenian who earned his living by dentistry, but never parted with the brush and palette and created many paintings, executed with professional skill and refined taste. It can be said that medicine was a means of existence for him, and painting was spiritual food. Unfortunately, only a few artistic articles devoted to him and which are at our disposal have been preserved, either very little was written, or they simply were not preserved. Mostly in the memories of relatives and friends of the family there is information about Massis Armen Bahadorian. His paintings that have come down to us testify to his achievements in the field of painting.
Keywords: Masis Armen Bahadorian; exile; Genocide; College Murad Raphaelian; Chicago; Arnold Turtle; Paula Bahador; still life